Work Ethic, Organizational Culture, and Employee Performance: A Mediated Framework of Job Satisfaction in Local Government Institutions - Luh Kartika Ningsih; Ni Luh Putu Reny Prajna Dewi; A.A.N. Eddy Supriyadinata Gorda; Komang Ary Pratiwi (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the influence of work ethic and organizational culture on employee performance, with job satisfaction serving as an intervening variable. A quantitative research design was employed, and data were collected through questionnaires administered to 140 employees at the Department of Culture of Buleleng Regency. The results indicate that both work ethic and organizational culture significantly affect employee performance and job satisfaction. Furthermore, job satisfaction functions as a mediating variable that strengthens the relationship between work ethic, organizational culture, and employee performance. The findings underscore that a strong work ethic is positively associated with higher job satisfaction, while a supportive organizational culture—characterized by cooperation and open communication—also contributes to increased satisfaction. Additionally, both organizational culture and work ethic directly enhance employee performance, highlighting the importance of motivation and a positive work environment. Overall, the study emphasizes the critical role of fostering a constructive organizational climate to improve employee satisfaction and performance.